Vitrification of human embryos previously cryostored by either slow freezing or vitrification results in high pregnancy rates - Stanger, J.; Wong, J.; Conceicao, J.; Yovich, John (2012)
Occasionally, clinical scenarios arise where embryos, previously cryostored and warmed, need to be recryopreserved. The outcome of 30 such transfer cycles from 25 women where embryos were recryopreserved is detailed. In 16 cases, embryos were initially cryopreserved by slow freezing and in 14 cases by vitrification. The cryopreservation stages were the pronuclear stage (n = 16), day-3 cleavage stage (n = 12), blastocyst (n = 1) and oocytes (n = 1). All recryopreservation was by Cryotop-based vitrification. From this mixed source, 30/31 twice-cryopreserved embryos survived warming and were transferred, resulting in 13 pregnancies, 11 deliveries with normal gestational age and birthweight, one pre-term birth at 33 weeks and two miscarriages. There were no malformations reported for the live births. Recryopreservation using vitrification by CryoTop has been used in a variety of clinical scenarios to preserve surplus cryopreserved embryos. The current study, although limited in numbers, resulted in high survival rates, clinical pregnancy rates similar to once-cryopreserved embryos and healthy live births independently of the initial stage and cryopreservation method. The technique may increasingly be applicable to elective single-embryo transfer and blastocyst transfer to maximize the pregnancy rate while minimizing the number of cryopreserved embryo transfers. © 2011 Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.